Exaggerated BMP4 Signaling Alters Human Airway Basal Progenitor Cell Differentiation to Cigarette Smoking-related Phenotypes - Zuo, Wu-Lin (Eur Respir J, 2019)
Airway remodeling in chronic obstructive pulmonary disease (COPD) originates, in part, from smoking-induced changes in airway basal stem/progenitor cells (BC). Based on the knowledge that the bone morphogenetic protein 4 (BMP4) influences epithelial progenitor function in the developing and adult mouse lung, we hypothesized that BMP4 signaling may regulate the biology of adult human airway BC relevant to COPD. BMP4 signaling components in human airway epithelium were analyzed at the mRNA and protein levels, and the differentiation of BC was assessed using the BC expansion and air-liquid interface models in the absence/presence of BMP4, BMP receptor inhibitor and/or siRNAs against BMP receptors and downstream signaling. The data demonstrates that in cigarette smokers, BMP4 is up-regulated in ciliated and intermediate undifferentiated cells and expression of the BMP4 receptor BMPR1A is enriched in BC. BMP4-induced BC to acquire a smoking-related abnormal phenotype in vitro mediated by BMPR1A/Smad signaling, characterized by decreased capacity to differentiate into the normal mucociliary epithelium, while generating squamous metaplasia. In summary, exaggerated BMP4 signaling promotes cigarette smoking-relevant airway epithelial remodeling by inducing abnormal phenotypes in human airway BC progenitor cells. Targeting of BMP4 signaling in airway BC may represent a novel target to prevent/treat COPD-associated airway disease.